Effect of a home‐based physical activity program on metabolic syndrome in Ghanaian adults with type 2 diabetes: Protocol for a feasibility randomized controlled trial - Mohammed Amin; Debra Kerr; Yacoba Atiase; Misbah Muhammad Samir; Andrea Driscoll (Wiley, 2024)
Abstract Aim To describe the protocol of a feasibility trial designed to test the preliminary effect of a 12‐week culturally appropriate physical activity programme on metabolic syndrome markers and quality of life in Ghanaian adults with type 2 diabetes (T2DM). Design Feasibility randomised controlled trial. Methods Through random allocation, 90 adults with T2DM will be allocated to either the control group (CG) (n = 45) or the intervention group (IG) (n = 45). The IG will receive the physical activity programme in addition to their usual diabetes care; those in the CG will receive their usual diabetes care. Measurements will be performed at baseline and 12‐week follow‐up. The primary outcome is a change in metabolic syndrome markers in the IG compared to the CG. Secondary outcomes are: (a) a change in quality of life in the IG compared to the CG, (b) the feasibility of implementation. Results Findings will inform the design of a future large‐scale trial. Patient or Public Contribution Patients with T2DM and their healthcare professionals contributed to this study protocol by participating in semi‐structured interviews towards the design of the physical activity programme. Clinical Trial Registration Number The trial is registered in the Australian and New Zealand Clinical Trial Registry (registration number: ACTRN12622000323729p).